Analisis Strategi Pengembangan Usaha Jasa Kebersihan: Studi Kasus Usaha Jasa Sini Sa Clean - Wahyul; Rita Yunus; Kalvin A. Parinding; Yunus Sading; Musdayati (ManBiz: Journal of Management and Business, 2024)
The cleaning service business SINI sa CLEAN is a business that has quite promising potential for development, even though it is very promising, SINI sa CLEAN is currently unable to compete in a broad scope. SINI sa CLEAN must be able to develop and continue to innovate so that it can survive and be able to compete. So an appropriate development strategy is needed. The type of research used in this research is descriptive qualitative and the data sources in writing this article were taken from primary data and secondary data. The analysis technique used in this research is the SWOT analysis technique, recording and observation to produce accurate information. The aim of this research is to determine the internal and external factors of the SINI sa CLEAN cleaning service business to find out the business development strategy and to find out the SINI sa CLEAN cleaning service business development strategy. The research results show that the total internal factors of strengths and weaknesses as the X axis are 0.73, while the total external factors of opportunities and threats as the Y axis are 2.83. So the strategic position for developing the SINI sa CLEAN cleaning service business is in quadrant I, namely in the S-O strategy position which has the strength and opportunity to be able to develop the SINI sa CLEAN cleaning service business.